RANCANG BANGUN 3D PRINTER CORE XY MENGGUNAKAN RAMP 1.4 BERBASIS ATMEGA 2560 - Budiastra, I Nyoman; Feryanda Frasiska, I Gede (Jurnal SPEKTRUM; Vol 7 No 2 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i02.p8, 2020)
Additive,Layer,Manufacturing,or,better,known,as,3D,printers,is,.the,process,of,combining,materi als,to build,objects,from,3D,model,data,with,layer,by,layer. In the development process, a new product prototype, 3D Printing, is a machine that plays a big role in the 2 and 3 dimensional,creation,process,in,the,product,design,process.,The,quality,of,printouts,and,timeefficient, in,making,3D,modeling,produced,becomes,more,effective,and,optimal.,The,purpose,of, the,study,is,to,examine,the,effectiveness,of,the,3D.printer.system.design,work using a shield type XY Ramp Core 1.4 based atmega 2560 and know the quality of the 3D printer prints. This research is a type of design activity, the results of data analysis using the results of 3D modeling are processed using a 3D printer and have a value of size accuracy as evidenced by the results of 3D measurements using calipers, It can be concluded that the 3D printer machine with,the,XY,belt,core,system,uses,Atemega,2560,based Ramp 1.4 which is made suitable for use in the 3D modeling process of,3D,modeling,measurements,using,calipers.